2015
DOI: 10.1128/ec.00050-15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Aspergillus fumigatus Biofilm Extracellular Matrix by Solid-State Nuclear Magnetic Resonance Spectroscopy

Abstract: dAspergillus fumigatus is commonly responsible for lethal fungal infections among immunosuppressed individuals. A. fumigatus forms biofilm communities that are of increasing biomedical interest due to the association of biofilms with chronic infections and their increased resistance to antifungal agents and host immune factors. Understanding the composition of microbial biofilms and the extracellular matrix is important to understanding function and, ultimately, to developing strategies to inhibit biofilm form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 42 publications
4
75
0
Order By: Relevance
“…This would suggest the locus of phage action is something specific for hyphae or extracellular matrix (Reichhardt et al, 2015). Consistent with this, our birefringence measurements and confocal microscopy studies indicate that Pf4 forms an ordered layer on Af biofilms.…”
Section: Discussionsupporting
confidence: 76%
“…This would suggest the locus of phage action is something specific for hyphae or extracellular matrix (Reichhardt et al, 2015). Consistent with this, our birefringence measurements and confocal microscopy studies indicate that Pf4 forms an ordered layer on Af biofilms.…”
Section: Discussionsupporting
confidence: 76%
“…fumigatus has shown, in vivo and in vitro, the ability to form biofilms, or complex aggregates of organisms embedded within a polymer-rich extracellular matrix, which demonstrate increased antimicrobial resistance (32). Thus, there is a need for other therapeutic methods with mechanisms that differ from those of the common antifungal targets of ergosterol or cell wall biosynthesis.…”
mentioning
confidence: 99%
“…Similar to bacteria, fungi secrete polysaccharides, proteins, and lipids and form an extracellular matrix (biofilm) under stress conditions. A nuclear magnetic resonance (NMR) analysis of the A. fumigatus extracellular matrix indicated that modified polysaccharides are the main component (306), as found in Vibrio cholerae by those same authors. Although dioxygen diffusion is limited in bacterial (307) and fungal (308) biofilms, how these changes trigger differentiation at the cellular level is largely unknown.…”
Section: Transitions From Vegetative Growth To Asexual Developmentmentioning
confidence: 71%